Branched Bio‐Lubricant Base Oil Production through Aldol Condensation. Issue 21 (30th September 2019) - Norton, Angela M.; Liu, Sibao; Saha, Basudeb; Vlachos, Dionisios G.
Abstract: Currently, lubricant base oils are derived from petroleum, a nonrenewable feedstock that contributes to greenhouse gas emissions. Bioderived, renewable lubricant base oils can mitigate environmental challenges and offer superior cold flow properties by incorporating branches to the base oil's hydrocarbon backbone with an appropriate synthetic strategy. A strategy was developed to synthesize branched alkanes for lubricant base oil in two steps from 12‐tricosanone, obtained from bioderived fatty acids, and furfural, obtained from lignocellulosic biomass. The reaction pathway involves carbon–carbon coupling through aldol condensation followed by hydrodeoxygenation (HDO). Various solvents (non‐polar, aprotic and polar, protic) and reaction conditions were screened to achieve a maximum yield of 94.3 % of aldol condensation products, containing the majority of a C33 furan (79.5 %) followed by a C28 furan (14.8 %). Subsequent HDO of aldol condensation products over an Ir‐ReO x /SiO2 catalyst produced lubricant‐ranged branched alkanes (C28 and C33 ) with 61.4 % yield and small fractions (<11 %) of alkanes with carbon numbers between C15 and C10 . The viscous properties of the produced bio‐lubricant base oil were comparable to commercial petroleum‐derived Group III and Group IV base oils. This approach serves as a potential stepping‐stone to replace petroleumderived base oils and, in turn, reduce greenhouse gas emissions associated with current lubricant production. Abstract : Green lubricant : Branched alkanes for lubricant base oil are synthesized in two steps from 12‐tricosanone, obtained from bioderived fatty acids, and furfural, obtained from lignocellulosic biomass. The reaction pathway involves carbon–carbon coupling through aldol condensation followed by hydrodeoxygenation.